Adrenergic receptor stimulation suppresses oxidative metabolism in isolated rat islets and Min6 cells. (15th September 2018) - Kelly, Amy C.; Camacho, Leticia E.; Pendarvis, Ken; Davenport, Hailey M.; Steffens, Nathan R.; Smith, Kate E.; Weber, Craig S.; Lynch, Ronald M.; Papas, Klearchos K.; Limesand, Sean W.
Abstract: Insulin secretion is stimulated by glucose metabolism and inhibited by catecholamines through adrenergic receptor stimulation. We determined whether catecholamines suppress oxidative metabolism in β-cells through adrenergic receptors. In Min6 cells and isolated rat islets, epinephrine decreased oxygen consumption rates compared to vehicle control or co-administration of epinephrine with α2-adrenergic receptor antagonist yohimbine. Epinephrine also decreased forskolin-stimulated oxygen consumption rates, indicating cAMP dependent and independent actions. Furthermore, glucose oxidation rates were decreased with epinephrine, independent of the exocytosis of insulin, which was blocked with yohimbine. We evaluated metabolic targets through proteomic analysis after 4 h epinephrine exposure that revealed 466 differentially expressed proteins that were significantly enriched for processes including oxidative metabolism, protein turnover, exocytosis, and cell proliferation. These results demonstrate that acute α2-adrenergic stimulation suppresses glucose oxidation in β-cells independent of nutrient availability and insulin exocytosis, while cAMP concentrations are elevated. Proteomics and immunoblots revealed changes in electron transport chain proteins that were correlated with lower metabolic reducing equivalents, intracellular ATP concentrations, and altered mitochondrial membrane potential implicating a new role for adrenergic control of mitochondrial function and ultimately insulin secretion. Highlights: Epinephrine decreases oxidative metabolism in β-cells via α2-adrenergic receptors. Oxidative metabolism was reduced despite interruptions in cAMP and insulin exocytosis. Proteomics identified novel mitochondrial, ribosomal, and proteasomal protein targets. Epinephrine altered expression of electron transport chain proteins in β-cells. Epinephrine increased mitochondrial membrane potential and decreased ATP content.